Exploring the Causal Effects of Circulating ST2 and Galectin-3 on Heart Failure Risk: A Mendelian Randomization Study - Wang, Xizhi; Wang, Xingchen; Zhu, Jun; Liu, Yu; Zhuang, Lenan; Zhang, Zhe; Zhong, Danfeng; Zhang, Wenbin; Lai, Dongwu (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure (HF), primarily caused by conditions such as coronary heart disease or cardiomyopathy, is a global health problem with poor prognosis and heavy burden on healthcare systems. As biomarkers of myocardial injury and fibrosis, suppression of tumorigenicity 2 (ST2) and galectin-3 were recommended for prognosis stratification in HF guidelines. However, the causality between these two mediators and HF remains obscure. This study aimed to explore the causal relationship of genetically determined ST2 and galectin-3 with the risk of HF. Methods: We used the two-sample Mendelian randomization (MR) method, incorporating available genome-wide association summary statistics, to investigate the causal association of ST2 and galectin-3 with HF risk. We applied inverse-variance weighted analysis as the main method of analysis. Results: In our final MR analysis, 4 single-nucleotide polymorphisms (SNPs) of ST2 and galectin-3 respectively were identified as valid instrumental variables. Fixed-effect inverse variance weighted analysis indicated that genetically predicted ST2 and galectin-3 were not causally associated with HF risk (odds ratio [OR] = 0.9999, 95% confidence interval [CI] = 0.994–1.004, p = 0.73; OR = 1.0002, 95% CI = 0.999–1.001, p = 0.60, respectively). These findings were robust in sensitivity analyses, including MR-Egger regression and leave-one-out analysis. Conclusions: This MR study provided no evidence for the causal effects of ST2 and galectin-3 on HF risk.